GUIDED TISSUE REGENERATION IN APICAL MICROSURGERY - Ferreira, Luciana L. [UNESP]; Bernabé, Pedro F. E. [UNESP]; Cintra, Luciano T. A. [UNESP] (My University, 2020)
Endodontic treatment aims to eliminate bacterial infection of root canal. However, the infection persists in some cases even after endodontic treatment. Periradicular surgery is an established treatment option in endodontics. Guided tissue regeneration (GTR) has been proposed in conjunction with apical surgery in order to obtain better bone healing. The fundamental principle of this technique is the prevention of the invasion of the bony defect by faster replication of junctional and gingival epithelial cells with the help of a barrier membrane placed over the material grafted in the defect. This protection facilitates the proliferation of cells of the periodontal ligament and alveolar bone in the defect, leading to the regeneration of bony defects. Techniques have been developed to enhance the GTR. However, the use of GTR technique should not become a routine procedure, since the periosteum is itself a barrier to epithelial and connective tissue cells. With respect to the membranes used in GTR, the literature has shown some preference to resorbable membranes and natural bone mineral for intra-bony defect filling. The aim of this review is to evaluate and compare the results of various studies that used the GTR, advantages and disadvantages of GTR, and the use of membranes and grafts.
Keywords: apical surgery; grafts; gtr; membranes